Correlation between the length and breadth of the nose and the face in different races - Vasanthan, Pravin; Tang, Lorna Pueh Mae; Mohd Zulkifli, Maryam; Mohd Adnan, Mohd Jazlan; Narayanan, Prepageran (Faculty of Medicine, University of Malaya, 2002)
This study is aimed at determining whether there exists a correlation between the relative dimensions of the nose and the face. Through this study, we hoped to give a normal range for the different races in Malaysia. We randomly chose 100 Malay, 50 Chinese and 50 Indian subjects. We chose equal numbers of male and female subjects, mainly in their 20's and 30's. There is a correlation between the length of the nose and the face among Malays, with 78% of the subjects measured having a nose:face ratio of less than 0.27. There is also a correlation between the breadth of the nose and the face among Malays, with 670/0 of the subjects having a ratio of less than 0.28. Similar correlations were found with Chinese and Indian subjects. The length and breadth of the nose in relation to the face is greater in males than in females. Further research is required before conclusive evidence is found for the existence or non existence of a correlation between the length and breadth of the nose and face in the different races in Malaysia.